A Resource Allocation and Evaluation Model for Providing Services to the Mentally Retarded - Heiner, Karl; Wallace, William A.; Young, Kevin (Management Science, 1981)
Legal decisions in the mental health field, and the process of deinstitutionalization have brought about an increasingly complex system of service delivery for the mentally retarded. We present a linear programming model to assist in managing such delivery systems. The usefulness and applicability of the model has been tested in Minnesota. We discuss how the procedure can be applied elsewhere. The model uses available measures of program efficiency and effectiveness, and transforms them into a form meaningful to the administrator who must make budgeting decisions and evaluate programs. In addition, with the help of this model, the administrator can incorporate important equity considerations into the management process.